EXTERNAL FACTORS ON THE BENEFITS OF ADOPTING E-COMMERCE TO MSMEs IN PALEMBANG AND DKI JAKARTA - Hardiyansyah; Aries, Aries; Muchardie, Brian Garda; Rillia, Anneke (Universitas Majalengka, 2023)
now considered a bridge for MSME players to carry out marketing with a wider range even to international markets and is one of the factors for the rise of Indonesian MSMEs, as well as the growth of the digital economy in Indonesia. This paper examines how perceived value and perceived benefits affect cost reduction and consumer orientation in MSMEs in Jakarta and Palembang in adopting E-commerce. There were 101 respondents who filled out the questionnaire with data analysis using the Partial Least Square (PLS) Structural Equation Model (SEM). The findings from this study indicate that the perceived benefits of customers will significantly affect cost reduction and can increase customer orientation, conversely competitive value can significantly affect customer orientation, but has no significant effect on cost reduction. The research results are expected to be a benchmark for MSMEs in adopting E-commerce.